"Zátopek" – komiksowa codzienność długodystansowca - Guzek, Mariusz (Załącznik Kulturoznawczy, 2023)
Zátopek: The Comic Version of the Everyday Life of a Long-distance Runner The comics signed by scriptwriter Jan Novák and illustrator Jaromír 99 follow a particularly well-thought-out authorial strategy. They tell the story of post-war Czechoslovakia, their protagonists are authentic figures, and their approach has little in common with the uncritical glorification so often found in (not only graphic) biographies. Created in 2016, the first of the works is dedicated to Emil Zátopek, a long-distance runner, three-time gold medalist at the Helsinki Olympics, and a man who got caught up in the political realities of the 20th century. The article analyzes the various contexts of diegetic conditioning (including the rituals of everyday life inscribed in the narrative), the critical reception of the book in the Czech Republic, and the correspondence between the sensibilities of the authors and other modes of memory management in a field explored in (popular) culture.